Analytical and numerical case studies on tailoring stiffness for the design of structures with displacement control - Trautwein, Axel; Prokosch, Tamara; Senatore, Gennaro; Blandini, Lucio; Bischoff, Manfred (Frontiers in Built Environment, 2023)
This paper discusses the role that structural stiffness plays in the context of designing adaptive structures. The focus is on load bearing structures with adaptive displacement control. In particular, in a design principle that minimizes actuation effort. By making the structure as stiff as possible against external loads and as flexible as possible against the effect of actuation. This rationale is tested by means of simple analytical and numerical case studies of academic benchmark problems.